PERANAN SEKRETARIAT DPRD DALAM MENDUKUNG FUNGSI DPRD (STUDI DI SKRETARIAT DPRD KOTA TOMOHON) - RINDENGAN, BRYAN RIZKY; Tulusan, Femmy; Ruru, Joorie Marhaen (Sam Ratulangi University, 2015)
ABSTRACT: In accordance with the mandate of Law Number 32 Year 2004 on Regional Governmentand Government Regulation No. 41 of 2007 concerning the regional Organization, that the ParliamentSecretariat is area that has the task to provide services administrative to Parliament, so the ParliamentSecretariat has an important role in supporting implementation of the functions of Parliament. In thisregard, this study to answer the question